Beam structures : classical and advanced theories - Carrera, Erasmo; Giunta, Gaetano; Petrolo, Marco (Hoboken, N.J. : Wiley, 2011)
'Present a new, unified approach to both classical and advanced beam theory that is becoming established and recognised globally as the most important contribution to the field in the last quarter of a centuryBeam Structures: Classical and Advanced Theories proposes a new original unified approach to beam theory that includes practically all classical and advanced models for beams and which has become established and recognised globally as the most important contribution to the field in the last quarter of a century. This approach overcomes the problem of classical formulae that require different formulas for tension, bending, shear and torsion; it can be applied to any beam geometries and loading conditions, reaching a high level of accuracy, and can tackle problems that in most cases are solved by employing plate/shell and 3D formulations. Beam Structures: Classical and Advanced Theories presents both the classical and advanced beam theories in a form that is very suitable for computer implementation It is accompanied by dedicated software MUL2 that is used to obtain the numerical solutions in the book, allowing the reader to reproduce the examples given in the book as well as to solve other problems of their own. The authors also include a number of static and dynamic problems and solutions that serve to further illustrate the advanced theories presented'--
'This book details classical and modern beam theories'--
Front Matter -- Fundamental Equations of Continuous Deformable Bodies -- The Eulerb6(BBernoulli and Timoshenko Theories -- A Refined Beam Theory with In-Plane Stretching: The Complete Linear Expansion Case -- EBBT, TBT, and CLEC in Unified Form -- Carrera Unified Formulation and Refined Beam Theories -- The Parabolic, Cubic, Quartic, and -Order Beam Theories -- CUF Beam FE models: Programming and Implementation Issue Guidelines -- Shell Capabilities of Refined Beam Theories -- Linearized Elastic Stability -- Beams made of Functionally Graded Materials -- Multi-Model Beam Theories via the Arlequin Method -- Guidelines and Recommendations -- Index.s
Includes bibliographical references and index.
Print version record.
Keywords: Girders; Electronic apparatus and appliances -- Vibration; Electronic books; Electronic books